2003
DOI: 10.1002/ccd.10601
|View full text |Cite
|
Sign up to set email alerts
|

Superior vena cava syndrome secondary to saphenous venous graft aneurysm with right atrial fistula

Abstract: Mega-aneurysms of saphenous vein grafts (SVGs) to coronary arteries are rare complications of bypass surgery. We report the development of superior vena cava syndrome secondary to an SVG mega-aneurysm with concomitant fistulous communication to the right atrium. Successful treatment was achieved by coil embolization and chronic anticoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Our literature review identified 107 patients [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95]. The demographic, clinical and pathological features are summarized in ...…”
Section: Resultsmentioning
confidence: 99%
“…Our literature review identified 107 patients [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95]. The demographic, clinical and pathological features are summarized in ...…”
Section: Resultsmentioning
confidence: 99%
“…Reported time interval of development of this complication is about 10-20 years postoperatively. Among them, the presence of a fistulous communication between the SVG aneurysm and one of the heart chambers is extremely rare and only 7 cases have been reported [1][2][3][4][5][6][7]. In six cases of them, the SVG aneurysms were connected to the right atrium, and in the seventh, it was connected to the To the best of our knowledge, this is the first report that the SVG aneurysm was connected to the LA.…”
Section: Discussionmentioning
confidence: 90%
“…SVG aneurysms may be noted incidentally as a hilar or mediastinal mass on imaging [6]. Clinical sequelae may include thrombotic emboli producing myocardial ischaemia [2], compression of the right atrium [7], pulmonary artery or superior vena cava [8][9][10][11], arrhythmias [7] and rupture [4,10,12-15] with haemothorax or cardiac tamponade [14].…”
Section: Ild Dilatation Of Saphenous Vein Grafts (Svg) Hasmentioning
confidence: 99%
“…Most reported cases have involved the right atrium [5,9,[16][17][18][19][20] and an adjacent right coronary artery (RCA) graft: communications with the right ventricle [ …”
Section: Ild Dilatation Of Saphenous Vein Grafts (Svg) Hasmentioning
confidence: 99%